THE THE EFFECTS OF PERCEIVED EASE OF USE, PERCEIVED SECURITY, AND PERCEIVED SATISFACTION ON INITIAL TRUST OF BRI MOBILE BANKING USERS (CUSTOMER STUDY IN SAMARINDA CITY) - Prajna Dyah Kinanti; Ana Noor Andriana (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
The purpose of this study was to examine the effect of perceived ease of use, perceived security, and trust on customer satisfaction using BRI mobile banking in Samarinda. This study uses a quantitative approach to the type of associative research. The number of samples used was 96 respondents using the purposive sampling method. The criteria for respondents in this study were BRI customers who are domiciled in the city of Samarinda and are over 18 years old and have been using BRI mobile banking for the last 6 months. The analysis technique used is data quality test, classic assumption test, multiple linear regression test, and hypothesis testing which is processed using the SPSS version 22 application. From the test results it is known that perceived security and perceived satisfaction have a positive and significant effect on the initial trust of BRI mobile banking users both partially and simultaneously, while perceived ease of us does not have a partial significant effect on the initial trust of BRI mobile banking users. So it can be concluded that perceived security and perceived satisfaction affect the initial trust level of BRI mobile banking customers.